PERAN UMKM PADA SEKTOR KULINER DALAM PENINGKATAN PENDAPATAN MASYARAKAT DI DESA SEROMBOU INDAH KECAMATAN RAMBAH HILIR - Elvarisa, Yola; Anwar, Arfianti Novita; Makmur, Makmur (Komunitas Manajemen Kompetitif, 2026)
This study aims to determine the role of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in increasing community income in Serombou Indah Village, Rambah Hilir District. This study uses a qualitative approach with data collection techniques through interviews, observation, and documentation. Informants in this study amounted to 15 MSMEs in the culinary sector who run businesses in Serombou Indah Village. The results of the study indicate that MSMEs in the culinary sector have a significant role in increasing community income. Culinary MSMEs are able to create small-scale employment opportunities by involving family members and the surrounding environment, encourage economic development through business development efforts, and create economic equality by utilizing local raw materials. In addition, income obtained from culinary MSMEs is able to meet the household needs of business actors, both as a primary and additional source of income, and contribute to the village economic cycle. Thus, MSMEs in the culinary sector play a role as one of the drivers of the village economy in increasing community income in Serombou Indah Village, Rambah Hilir District, although they still face limitations in capital and marketing.